2023
DOI: 10.1002/adfm.202211730
|View full text |Cite
|
Sign up to set email alerts
|

Organic Conjugated Trimers with Donor–Acceptor–Donor Structures for Photocatalytic Hydrogen Generation Application

Abstract: Organic donor-acceptor-donor (D-A-D) polymers or small molecules are widely investigated in organic solar cells (OSC) due to their broad light absorption, narrow band gap, excellent charge mobility and exciton seperation at the interface. However, studies of conjugated small molecules with D-A-D molecule structures as photocatalytically active materials are still rare. In this work, we give an unprecedented demonstration that photocatalytic activity can in fact be affected by tuning the D and A.Especially, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 48 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Eric Cloutet et al also constructed a D‐A‐D conjugated molecule using carbazole (C) as the D unit and quinoxaline (Q) and benzothiadiazole (B) as the A unit. [ 59 ] As in Figure 3c , the CBC and CQC trimers show stable photocatalytic hydrogen evolution performance.…”
Section: Intramolecular D‐a Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eric Cloutet et al also constructed a D‐A‐D conjugated molecule using carbazole (C) as the D unit and quinoxaline (Q) and benzothiadiazole (B) as the A unit. [ 59 ] As in Figure 3c , the CBC and CQC trimers show stable photocatalytic hydrogen evolution performance.…”
Section: Intramolecular D‐a Interactionsmentioning
confidence: 99%
“…As in Figure 2b , quinoxaline (Q) and benzothiadiazole (B) are chosen as A units, and 3,4‐ethylenedioxythiophene (E) and thiophene (T), both with strong electron‐donating ability, are used as D units, respectively. [ 59 ] The D‐A‐D molecule (EBE) comprising E and B units performs the best photochemical performance with the photocatalytic hydrogen evolution rate of 142 µmol g −1 h −1 . Naphthalene diimide (NDI) is a classical n‐type semiconductor with superior electron‐withdrawal and charge transport properties.…”
Section: Intramolecular D‐a Interactionsmentioning
confidence: 99%
“…4a). 48,49 In the presence of the triethanolamine (TEOA) sacrificial donor, the rod-like aggregates photoproduced H 2 with an AQY of approximately 2% (400-450 nm), which was attributed to a combination of broad visible light absorption, a small band gap, wettability, and long exciton lifetimes. Furthermore, it was observed that no additional co-catalyst was added, and the residual palladium from cross-coupling was found to impact the photocatalytic activity.…”
Section: Precipitationmentioning
confidence: 99%
“…11,17 Signicantly, recent studies have suggested that the construction of intramolecular donor-acceptor (D-A) conjugated polymers by embedding donor/acceptor groups may be a potential method for improving photocatalytic performance. [18][19][20] In general, the potential difference between donor and acceptor groups can effectively improve the separation of photoinduced charges. 21,22 Although D-A conjugated polymers are promising semiconductors for photocatalytic applications, construction methods are usually too complex, and the mechanisms of action are not satisfactorily revealed.…”
Section: Introductionmentioning
confidence: 99%